Effects of Body Mass Index on Hypertriglyceridemia Associated with Oral Bexarotene Therapy: A Post Hoc Analysis of an Open-Label Comparative Clinical Study of Combined Bexarotene and Phototherapy Versus Bexarotene Monotherapy for Japanese Patients with Cutaneous T-Cell Lymphoma - Akimasa Sanagawa; Tomoaki Hayakawa; Aya Yamamoto; Yuji Hotta; Yoko Furukawa-Hibi; Akimichi Morita (Adis, Springer Healthcare, 2024)
Abstract Background Bexarotene, which has been approved for use in Japan since 2016, is an effective drug for cutaneous T-cell lymphoma; however, careful management is imperative because of its adverse events. We previously demonstrated the severity of bexarotene-associated hypertriglyceridemia and the need for bexarotene dose reduction for patients with cutaneous T-cell lymphoma and high body mass index (BMI); however, high BMI does not affect the efficacy of combined bexarotene and phototherapy treatment. Objective This study aimed to verify the effects of BMI on hypertriglyceridemia associated with oral bexarotene therapy. Methods We conducted a post hoc analysis of data from a previous randomized, open-label clinical study that compared combined bexarotene-phototherapy treatment with bexarotene monotherapy for cutaneous T-cell lymphoma by dividing patients into two groups based on BMI (<23 kg/m2 and ≥23 kg/m2). Results No statistically significant association was observed between patients with BMI ≥23 kg/m2 and severe hypertriglyceridemia; however, there was a significant association between BMI ≥23 kg/m2 and severe hypertriglyceridemia for patients who received bexarotene monotherapy, but not for those who received combined bexarotene-phototherapy treatment. The exact reasons for the discrepancies between the results of this thorough analysis and those of our past research are unclear. However, high BMI may be a risk factor for hypertriglyceridemia. Additional unidentified risk factors could also affect treatment outcomes. Conclusion High BMI is the primary reason for hypertriglyceridemia-associated bexarotene dose reduction; however, unexplored risk factors other than high BMI could exist.